Enhanced Electrochemical Performance of LiNi0.8Co0.1Mn0.1O2 with SiO2 Surface Coating Via Homogeneous Precipitation. Issue 22 (18th November 2021) - Dou, Lintao; Hu, Pu; Shang, Chaoqun; Wang, Heng; Xiao, Dongdong; Ahuja, Utkarsh; Aifantis, Katerina; Zhang, Zhanhui; Huang, Zhiliang
Abstract: Ni‐rich LiNi0.8 Co0.1 Mn0.1 O2 (NCM811) has been considered as a promising cathode material for high energy density lithium‐ion batteries. However, it experiences undesirable interfacial side‐reactions with the electrolyte, which lead to a rapid capacity decay. In this work, a homogeneous precipitation method is proposed for forming a uniform silicon dioxide (SiO2 ) coating on the NCM811 surface. The strong Si−O network provided a stable protective layer between the NCM811 active material and electrolyte to improve the electrochemical stability. As a result, the NCM811@SiO2 cathode showed superior cycling stability (84.9 % after 100 cycles at 0.2 C) and rate capability (142.7 mA h g −1 at 5 C) compared to the pristine NCM811 cathode (56.6 % after 100 cycles, 127.9 mA h g −1 at 5 C). Moreover, the SiO2 coating effectively suppressed voltage decay and pulverization of the NCM811 particles during long term cycling. This uniform coating technique offers a viable approach for stabilizing Ni‐rich cathode materials for high‐energy density lithium‐ion batteries. Abstract : Silica coated : An urea‐assisted homogeneous precipitation method is employed to constructing a uniform coating of amorphous SiO2 on the surface of NCM811 particles, and the SiO2 coating layer can effectively suppresses voltage decay and pulverization of the NCM811 particles during long term cycling. Benefiting from the chemically inert coating, NCM811@SiO2 shows superior cycling stability and rate capability compared to the pristine NCM811 cathode.